The role of the stress regime on microseismicity induced by overpressure and cooling in geologic carbon storage. Issue 5 (4th October 2016) - Vilarrasa, V.
Abstract: Fluid injection in deep geological formations usually induces microseismicity. In particular, industrial‐scale injection of CO2 may induce a large number of microseismic events. Since CO2 is likely to reach the storage formation at a lower temperature than that corresponding to the geothermal gradient, both overpressure and cooling decrease the effective stresses and may induce microseismicity. Here, we investigate the effect of the stress regime on the effective stress evolution and fracture stability when injecting cold CO2 through a horizontal well in a deep saline formation. Simulation results show that when only overpressure occurs, the vertical total stress remains practically constant, but the horizontal total stresses increase proportionally to overpressure. These hydro‐mechanical stress changes result in a slight improvement in fracture stability in normal faulting stress regimes because the decrease in deviatoric stress offsets the decrease in effective stresses produced by overpressure. However, fracture stability significantly decreases in reverse faulting stress regimes because the size of the Mohr circle increases in addition to being displaced towards failure conditions. Fracture stability also decreases in strike slip stress regimes because the Mohr circle maintains its size and is shifted towards the yield surface a magnitude equal to overpressure minus the increase in the horizontal total stresses. Additionally, cooling induces a thermal stress reduction in all directions, but larger in the out‐of‐plane direction. This stress anisotropy causes, apart from a displacement of the Mohr circle towards the yield surface, an increase in the size of the Mohr circle. These two effects decrease fracture stability, resulting in the strike slip being the least stable stress regime when cooling occurs, followed by the reverse faulting and the normal faulting stress regimes. Thus, characterizing the stress state is crucial to determine the maximum sustainable injection pressure and maximum temperature drop to safely inject CO2 . Abstract : Fracture stability represented by Mohr circles in the caprock and reservoir for normal faulting, strike slip and reverse faulting stress regime. The grey circles indicate the initial stress state, the orange circles correspond to the stress state when injecting CO2 in thermal equilibrium with the storage formation, and the blue circles show the stress state when injecting cold CO2 . The red lines represent the yield surface.